H₂O₂에 의해 유도된 HepG2 세포의 산화적 스트레스에 대한 신품종 방사선 돌연변이 블랙베리 γ-B201의 세포 보호 효과 - 조병옥(Byoung Ok Cho); 이창욱(Chang-Wook Lee); 소양강(Yangkang So); 진창현(Chang-Hyun Jin); 육홍선(Hong-Sun Yook); 변명우(Myung-Woo Byun); 정용욱(Yong-Wook Jeong); 박종천(Jong Chun Park); 정일윤(Il-Yun Jeong) (한국식품과학회지, 2014)
The objective of the present study was to investigate the chemical composition of anthocyanin-enriched extractof radiation-induced blackberry (Rubus fruticosus L.) mutant (γ-B201) as well as the protective effect of γ-B201 againstoxidative stress in vitro. The cytotoxicity, reactive oxygen species (ROS) scavenging capacity, and DNA damage wereassessed by WST-1 assay, flow cytometry, and comet assay, respectively. Lactate dehydrogenase, superoxide dismutase, andcatalase activities were determined by using a commercial kit. The in vitro results showed that γ-B201 increased the cellviability, reduction of lactate dehydrogenase release, and intracellular ROS scavenging capacity in hydrogen peroxide(H2O2)-treated HepG2 cells. Furthermore, treatment with γ-B201 attenuated DNA damage in H2O2-treated HepG2 cells andtreatment with γ-B201 restored the activity of superoxide dismutase and catalase in H2O2-treated HepG2 cells. Inconclusion, the present study suggests that γ-B201 blackberry extract can exert a significant cytoprotective effect againstH2O2-induced cell damage. KCI Citation Count: 6